Effectiveness of a preschool emotional education programme administered over 3 grades: a cluster randomised controlled trial. (May 2023) - San Pío, M.J.; Clotas, C.; Espelt, A.; López, M.J.; Bosque-Prous, M.; Juárez, O.; Bartroli, M.
Abstract: Introduction: Emotional education programmes are universal preventive strategies for health promotion, especially mental health. The aim of this study is to evaluate the effectiveness and implementation of '1, 2, 3, emoció!': a preschool-based programme designed to improve emotional competence and targeted to 3–5-year-old children in Barcelona during three academic years. Study design: Cluster randomised trial, using schools as clusters. Methods: The study's population included preschoolers 3-5 years old from Barcelona. Teachers offered the programme during one or three academic years in the intervention groups. We evaluated the emotional competence of each child at the beginning and the end of the academic year with the Emotional Competence Assessment Questionnaire (30–180 scale). We studied the implementation process and analysed the outcomes with nested linear regression models. Considering sociodemographic variables and implementation outcomes, we obtained the individual differences in emotional competence at the end of the school year—segregated by sex—for intervention and comparison groups. Results: 1586 children participated in the study. The emotional competence level increased significantly after one year (4.1 in boys; 5.6 in girls; P  < 0.05) and after three years of intervention (5.5 in boys; 8.0 in girls; P  < 0.01), compared to comparison group. The level of emotional competence was the highest for the 3-year intervention group: we obtained an average ECAQ score of 131.1 (95% CI 126.9–135.2) for boys and 141 (95% CI 137.2–144.9) for girls. We observed that an accurate implementation improved its results. Conclusions: The programme '1, 2, 3, emoció!' effectively increases preschool children's emotional competence, especially when the programme is rigorously implemented for three years.